2013
DOI: 10.1128/aac.00669-13
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing of Gentamicin-Resistant Campylobacter coli Isolated from U.S. Retail Meats Reveals Novel Plasmid-Mediated Aminoglycoside Resistance Genes

Abstract: bAminoglycoside resistance in Campylobacter has been routinely monitored in the United States in clinical isolates since 1996 and in retail meats since 2002. Gentamicin resistance first appeared in a single human isolate of Campylobacter coli in 2000 and in a single chicken meat isolate in 2007, after which it increased rapidly to account for 11.3% of human isolates and 12.5% of retail isolates in 2010. Pulsed-field gel electrophoresis analysis indicated that gentamicin-resistant C. coli isolates from retail m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 31 publications
3
54
0
Order By: Relevance
“…2. In general, the novel multidrug resistance island identified in this study showed a very low similarity with the segments of pN29701 (CP004067) and SX81 (JQ655275) (16,17) but was highly similar to the segment of pCG8245 (AY701528) (14). S1 pulsed-field gel electrophoresis (S1-PFGE) and Southern hybridization verified that the aph(2Љ)-If gene was located on the chromosome instead of a plasmid (data not shown).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…2. In general, the novel multidrug resistance island identified in this study showed a very low similarity with the segments of pN29701 (CP004067) and SX81 (JQ655275) (16,17) but was highly similar to the segment of pCG8245 (AY701528) (14). S1 pulsed-field gel electrophoresis (S1-PFGE) and Southern hybridization verified that the aph(2Љ)-If gene was located on the chromosome instead of a plasmid (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…The aacA/aphD gene encoding a bifunctional enzyme was associated with gentamicin resistance (16). Very recently, several variants of 2Љ-phosphotransferase accounting for gentamicin resistance were identified in Campylobacter in the United States (9,17).…”
mentioning
confidence: 99%
“…1). Similarly to the p11601MD region encompassing tet(O) and aphA-3, the corresponding region of pN29710-1 has a higher GC content than the rest of the plasmid, suggesting acquisition from another source via horizontal gene transfer (Chen et al, 2013). These findings suggest that the tet(O)-aphA-3 cassette in p11601MD represents a minimal antimicrobial resistance locus that can become expanded in other plasmids by insertion of additional genes.…”
Section: Organization Of P11601md and Pcr-based Detection Of Homologomentioning
confidence: 83%
“…However, the accompanying ORFs (designated ORFA and ORFB) associated with a putative transposase (IS607*) upstream of aphA-3 in pCJG9 (Gibreel et al, 2004) were not detected in p11601MD. In another example, the aphA-3 of p11601MD had 100% identity to a gene annotated as 3' aminoglycoside-phosphotransferase in plasmid pN29710-1 (55,127 nt) from C. coli strain CVM N29710 (Chen et al, 2013) (Fig. 1).…”
Section: Organization Of P11601md and Pcr-based Detection Of Homologomentioning
confidence: 97%
“…It allows a single test to replace several less efficient and more expensive technologies that require specialized training. For example, it is possible to extract serotype information from a bacterial pathogen genome along with antibiotic resistance patterns and the relatedness of strains in an outbreak (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). This will obviate the need to support multiple methodologies for the various pathogenic species.…”
Section: Outreach and Harmonization Effortsmentioning
confidence: 99%